2023
DOI: 10.1021/acs.jafc.3c00221
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Simulated Gastrointestinal Digestion Stability of a Neuroprotective Octapeptide WCPFSRSF and Prediction of Potential Bioactive Peptides in Its Digestive Fragments by Multiple Bioinformatics Tools

Abstract: WCPFSRSF, an octapeptide (Trp-Cys-Pro-Phe-Ser-Arg-Ser-Phe), has been reported to improve memory in mice, but its gastrointestinal stability is unclear. The objective of this study was to evaluate the gastrointestinal stability of peptide WCPFSRSF and explore the neuroprotective potential of its digestive fragments. Results showed that the content of WCPFSRSF after gastric and gastrointestinal digestion decreased to 71.64% and less than 1%, respectively. Furthermore, the antioxidant and neuroprotective ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…Collectively, the ability of peptides to inhibit neuroinflammation via JAK2/STAT3 signaling was graded as WCPF > WCP > SR. It was consistent with the fact that WCPF has a higher cell-survival-promoting ability than SR in SH-SY5Y cells . It may be related to the strong ADMET property and potential bioactivity of WCPF .…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Collectively, the ability of peptides to inhibit neuroinflammation via JAK2/STAT3 signaling was graded as WCPF > WCP > SR. It was consistent with the fact that WCPF has a higher cell-survival-promoting ability than SR in SH-SY5Y cells . It may be related to the strong ADMET property and potential bioactivity of WCPF .…”
Section: Discussionsupporting
confidence: 86%
“…The neuroinflammatory response is characterized by the activation of microglia and increased cytokine levels, which aggravate neuronal cell death and neurodegeneration . In a prior study, we found that peptide WCPFSRSF improved memory decline by preventing neuroinflammation, and WCPFSRSF predominantly decomposed into two groups of neuroprotective peptides with distinct characteristics in the gastrointestinal tract . Currently, the mechanisms underlying the differences between these peptides remain unknown.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, the antioxidant peptide, AEEEYPDL, was broken down into smaller peptides, AEEEY and PDL, after simulated gastrointestinal digestion, leading to the loss of its antioxidant activity. Zhao et al [ 110 ] investigated the impact of in vitro-simulated gastrointestinal digestion on the biological activity of the neuroprotective octapeptide, WCPFSRSF. They were able to identify eight novel peptides, namely, WCP, WCPF, WCPFS, PF, PFS, SR, SRS, and WCPFSRS, from the final digestive production.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%